Total Serum Antioxidant Capacity in Healthy Normal Weight and Asymptomatic Overweight Adults - Petelin, Ana; Tedeschi, Paola; Maietti, Annalisa; Jurdana, Mihaela; Brandolini, Vincenzo; Pražnikar, Zala Jenko (Experimental and Clinical Endocrinology & Diabetes, 2017)
Obesity and overweight are major contributors to the burden of chronic disease. Both are defined as abnormal or excessive fat accumulation and by increased production of free radicals leading to oxidative stress. The aim of the present study was to evaluate whether overweight and fat accumulation is associated with serum total antioxidant capacity (TAC) in men and women, irrespective of nutritional habits, nutrient intakes, physical activity, smoking, and other confounders, which may be responsible for modifying the association between serum TAC and overweight/obesity measures. This cross-sectional study was conducted on 60 normal weight and 60 overweight adults aged 25–49. All participants underwent standard anthromorphological measurements of body composition, blood pressure and biochemical measurements, aerobic capabilities assessment and dietary intake evaluation. TAC was measured by using the photochemioluminescence method. All data were analysed with SPSS software. Men had higher values of TAC than women and concentrations of TAC were significantly higher in overweight subjects compared to normal weight subjects. In the present study TAC tended to be increased by various metabolic risk factors, especially overweight/obesity parameters (body mass index, body fat), inflammation and increased serum levels of Cysteine, irrespective of nutritional habits, nutrient intakes, physical activity and smoking. Overweight and obesity at an early stage may stimulate TAC. Therefore, the elevation of TAC in overweight adults may be a compensatory response to oxidative stress, generated by reactive oxygen species.
Keywords: antioxidant capacity; overweight; oxidative stress; metabolic risk factors; asymptomatic population